Characterization of n-alkanes and n-alkylbenzenes from different sediments by Py-GC/MS. (2nd September 2017) - Zhang, Ting; Wang, Yongli; Wang, Zuodong; Wei, Zhifu; Qian, Yu; Sun, Zepeng; Wang, Gen
ABSTRACT: Sediments from a selection of source were systematically pyrolysed in two kinds of experiments (single stage and multi-stage) using analytical pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) in order to investigate the n -alkanes and n -alkylbenzenes obtained in pyrolysate volatiles. Our results show that the n -alkanes can be detected by Py-GC/MS, this may be related to the high molecular cleavage of the diverse organic matter constituents under the thermal conditions. And n -alkylbenzenes were also detected, probably produced in connection with n -alkanes, or products of their subsequent evolution. In addition, both sets of experimental results suggested that organic matter adsorbed in modern sediments differs from that in source rocks where organic matter is bound in kerogen, thus the primary stage of products in modern sediments is earlier than that in source rocks.